Leonidas Polk: warrior bishop of the Confederacy - Horn, Huston (University Press of Kansas, 2019)
"Second cousin to president James K. Polk, Leonidas Polk (1806-1864) joined the Episcopal Church in his senior year at West Point, and upon graduating enrolled in Virginia Theological Seminary. Shortly after being ordained as an Episcopal priest, he was appointed missionary bishop of the Southwest, then comprising lands west of the Mississippi, including Arkansas, Louisiana, and Texas. In 1841, he was elected Bishop of the newly formed Diocese of Louisiana. A native of Tennessee, Polk was instrumental in founding The University of the South in Sewanee, Tennessee in 1857. At the outbreak of the Civil War, Polk offered fellow West Point alumnus Jefferson Davis his services in the Confederate army. He was commissioned a major general in 1861. His command saw combat in the Western Theater at Shiloh, Perryville, Stones River, and Chickamauga, after which Polk was transferred to the East. On June 14, 1864, Polk and fellow generals were scouting enemy positions at Pine Mountain in Georgia when Polk was killed by Federal artillery fire. While Polk is a well-known figure, particularly among Civil War historians and buffs, no recent scholarly biography of Polk exists except for a revised dissertation, focusing on Polk's Episcopal identity and ecclesiastical career, published by Mercer University Press in 2006"--